2021
DOI: 10.1155/2021/8856048
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Variceal Ligation Monotherapy versus Combined Ligation and Sclerotherapy for the Treatment of Esophageal Varices

Abstract: Currently, endoscopic variceal ligation (EVL) monotherapy is the standard therapy for managing esophageal variceal hemorrhage. Patients generally need several sessions of endoscopy to achieve optimal variceal ablation, and the varices can recur afterward. Endoscopic injection sclerotherapy (EIS) is an older technique, associated with certain complications. This study aimed to evaluate the clinical efficacy of EVL alone versus combined EVL and EIS in the treatment of esophageal varices. This retrospective study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Prior to PSM, our study showed that patients treated with EVL plus EIS had significantly less varicose recurrence and rebleeding than patients treated with EVL alone, whether at 6-, 12-, or 18-month follow-up. Our results agree with Mansour et al and Wang et al (2,10,14,15). Compared with EVL alone, the EVL plus EIS group had a significant advantage in variceal recurrence and rebleeding for the following principal reasons.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Prior to PSM, our study showed that patients treated with EVL plus EIS had significantly less varicose recurrence and rebleeding than patients treated with EVL alone, whether at 6-, 12-, or 18-month follow-up. Our results agree with Mansour et al and Wang et al (2,10,14,15). Compared with EVL alone, the EVL plus EIS group had a significant advantage in variceal recurrence and rebleeding for the following principal reasons.…”
Section: Discussionsupporting
confidence: 92%
“…Mansour et al and Harras et al performed sclerotherapy at each variceal vein 3-5 cm and 5-10 cm from the esophagogastric junction and then injected sclerosing agent into the variceal vein 2-3 cm above the gastroesophageal junction (14,24). Wang et al ligated each vein and then injected 2-5 ml of a sclerosing agent into the variceal vein at the time of ligation, 2-3 cm from the upper part of the band (10). In our study, we first performed EVL at the nearest location near the gastroesophageal junction, releasing 5-7 bands depending on the varices to maximize blockage of blood flow.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, most complications can also be managed with endoscopic interventions (29). On the other hand, other studies show that combined variceal ligation and sclerotherapy had less rebleeding rates and recurrence at six months and less chest pain and was more cost-effective compared to endoscopic variceal ligation alone in the treatment of gastroesophageal varices (30).…”
Section: Discussionmentioning
confidence: 99%